Chū khamphī Mūladīkā Sangkhinī : pariwat čhāk khamphī bailān ʻaks̨̄on Kh̨̄om pen Thai - Ānandà, Maha Thera, ca. 5th cent (s.n., 1974)
Super-commentary on Aṭṭhasālinī by Buddhaghosa, a commentary on Abhidhammapiṭaka, canonical text of Theravada Buddhism; comrpises the first part, Dhammasāngani.